PERSONAL ETHICS AND TIME MANAGEMENT ON STUDENTS' LEARNING HABITS IAIN LANGSA - Lathifah Hanum; Hasan Asari; Syafaruddin Syafaruddin (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This paper aims to analyze personal ethics and time management on the study habits of students of the Islamic Religious Education Study Program (PAI), the Faculty of Tarbiyah and Teacher Training (FTIK) of the Langsa State Islamic Institute (IAIN). This study uses a qualitative approach with phenomenological methods. The data collection was done by using interviews, observation, and documentation studies. Furthermore, the data were analyzed using data reduction techniques, narrative data presentation, conclusion drawing and data verification. The results of this study indicate that (1) students understand and practice learning ethics well in accordance with the ethical guidelines of students at IAIN Langsa, (2) students' time management in learning is divided into two, namely students who actively make daily activity schedule, plans and targets they want to achieve. achieved, while there are students who are in the inactive category in managing study time, and (3) the study habits of PAI FTIK IAIN Langsa students are classified into 2, namely 73% are active and enjoy learning alone and 27% are active and enjoy participating in group learning.